A Randomized, Double-blinded, Placebo-controlled Trial of Sitagliptin for Reducing Inflammation and Immune Activation in Treated and Suppressed Human Immunodeficiency Virus Infection. (10th December 2018) - Dubé, Michael P; Chan, Ellen S; Lake, Jordan E; Williams, Brett; Kinslow, Jennifer; Landay, Alan; Coombs, Robert W; Floris-Moore, Michelle; Ribaudo, Heather J; Yarasheski, Kevin E
Abstract: Background: Dipeptidyl peptidase-4 (DPP-4) inhibitors have pleotropic anti-inflammatory and immune regulatory effects in addition to glucoregulation. We evaluated inflammation and immune markers in suppressed human immunodeficiency virus (HIV) infection during treatment with the DPP-4 inhibitor sitagliptin. Methods: Virologically suppressed adults with HIV without diabetes on stable antiretroviral therapy (ART) with ≥100/μL CD4 cells were randomized to 16 weeks of sitagliptin 100 mg/day vs placebo in a multicenter trial. The primary endpoint was the change in plasma soluble CD14 (sCD14) from baseline to week 15–16. Results: Ninety participants were randomized, and 42 from each arm were included in per-protocol analyses. Participants were 45% non-Hispanic white, 38% non-Hispanic black, and 15% Hispanic, with a median age of 51 years; 83% were male; and the median CD4 count was 602 cells/μL. At week 15–16, there was no difference in sCD14 change between the 2 arms ( P = .69). Relative to placebo, the sitagliptin arm had 47% greater decline in CXCL10 (95% confidence interval, –57% to –35%) at week 15 ( P < .001). There were no significant between-arm differences in other soluble biomarkers, total CD4 and CD8 counts, or markers of lymphocyte or monocyte activation. Sitagliptin was well tolerated. Conclusions: Sixteen weeks of sitagliptin had no effect on sCD14 levels in virologically suppressed participants with HIV. CXCL10, a chemokine involved in atherogenesis that predicts non-AIDS events during ART, declined markedly with sitagliptin. This suggests that DPP-4 inhibition has the potential to reduce cardiovascular morbidity in treated HIV infection. Clinical Trials Registration: NCT01426438. Abstract : The immunomodulatory effects of the dipeptidyl peptidase-4 inhibitor sitagliptin were tested in virologically suppressed participants with HIV. There was no effect on the primary endpoint soluble CD14 or cellular activation, but levels of the proinflammatory chemokine CXCL10 fell by approximately 50%.